Enhanced Tumor Targeting and Radiotherapy by Quercetin Loaded Biomimetic Nanoparticles - Huang, Chunyu; Chen, Tongkai; Zhu, Daoming; Huang, Qinqin (Frontiers in Chemistry, 2020)
In Chinese traditional medicine, quercetin (QT) plays a fundamental role in the treatment of asthma, as an anti-allergen and for lowering blood pressure. Recent evidence suggests that QT can improve tumor radiosensitivity through multiple mechanisms. However, poor tumor tissue targeting ability and low water solubility of QT limit its usefulness in the treatment of cancers. Herein, we designed a novel drug delivery system (CQM) consisting of inner QT loaded mesoporous silica nanoparticles (MSNs) and outer cancer cell membranes (CM). The developed nanoplatform had strong anti-cancer effects under X-ray irradiation and a good QT loading characteristics. In addition, CQM effectively targeted tumor tissues. Results of in vitro and in vivo experiments demonstrated that the developed CQM drug delivery system has excellent tumor targeting ability and effectively inhibited tumor growth. Therefore, CQM platform realized targeted drug delivery and radiotherapy sensitization, which provided a newfangled idea to cancer treatment.